Structure and Dynamics of Confined C-O-H Fluids Relevant to the Subsurface: Application of Magnetic Resonance, Neutron Scattering, and Molecular Dynamics Simulations - Gautam, Siddharth S.; Ok, Salim; Cole, David R. (Frontiers in Earth Science, 2017)
Geo-fluids consisting of C-O-H volatiles are the main mode of transport of mass and energy throughout the lithosphere and are commonly found confined in pores, grain boundaries and fractures. The confinement of these fluids by porous media at the length scales of a few nanometers gives rise to numerous physical and chemical properties that deviate from the bulk behavior. Studying the structural and dynamical properties of these confined fluids at the length and time scales of nanometers and picoseconds respectively forms an important component of understanding their behavior. To study confined fluids, non-destructive penetrative probes are needed. Nuclear magnetic resonance (NMR) by virtue of its ability to monitor longitudinal and transverse magnetization relaxations of spins, and chemical shifts brought about by the chemical environment of a nucleus, and measuring diffusion coefficient provides a good opportunity to study dynamics and chemical structure at the molecular length and time scales. Another technique that gives insights into the dynamics and structure at these length and time scales is neutron scattering (NS). This is because the wavelength and energies of cold and thermal neutrons used in scattering experiments are in the same range as the spatial features and energies involved in the dynamical processes occurring at the molecular level. Molecular Dynamics (MD) simulations on the other hand help with the interpretation of the NMR and NS data. Simulations can also supplement the experiments by calculating quantities not easily accessible to experiments. Thus using NMR, NS and MD simulations in conjunction, a complete description of the molecular structure and dynamics of confined geo-fluids can be obtained. In the current review, our aim is to show how a synergistic use of these three techniques has helped shed light on the complex behavior of water, CO2, and low molecular weight hydrocarbons. After summarizing the theoretical backgrounds of the techniques, we will discuss some recent examples of the use of NMR, NS, and MD simulations to the study of confined fluids.